Cleft Palate - Kosowski, Tomasz R.; Weathers, William M.; Wolfswinkel, Erik M.; Ridgway, Emily B. (Seminars in Plastic Surgery, 2012)
Our understanding of cleft palates has come a long way over the last few decades. A better understanding of the long-term consequences of a cleft palate and its effect on speech development challenges surgeons to not only effectively repair the cleft, but to also restore function of the palate for adequate speech. Coordination with speech pathologists is integral for effective management of cleft palate patients, particularly as children begin to develop language. In this article, the authors review and summarize the various challenges and goals of cleft palate management.
Keywords: congenital; cleft palate; velopharyngeal insufficiency